2009
DOI: 10.1186/1752-1947-3-7271
|View full text |Cite
|
Sign up to set email alerts
|

Rare case of autonomic instability of the lower limb presenting as painless Complex Regional Pain Syndrome type I following hip surgery: two case reports

Abstract: IntroductionAccording to the International Association for the Study of Pain criteria of 1994, pain is a diagnostic requirement for Complex Regional Pain Syndrome type I. However, other authors have suggested that patients can rarely present with the sensory and vascular symptoms of Complex Regional Pain Syndrome without pain. This entity has not been reported following hip surgery in the English medical literature.Case presentationWe present two cases of Complex Regional Pain Syndrome-like symptoms following … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…Since its first description in 1916 [ 10 ], CRPS has been rarely described after hip surgery and can easily be ignored by the inexperienced physician [ 4 , 5 , 11 ]. Patman et al [ 12 ] reported 113 cases of post-traumatic pain syndrome of which only 18 had their diagnosis made by the treating physician.…”
Section: Discussionmentioning
confidence: 99%
“…Since its first description in 1916 [ 10 ], CRPS has been rarely described after hip surgery and can easily be ignored by the inexperienced physician [ 4 , 5 , 11 ]. Patman et al [ 12 ] reported 113 cases of post-traumatic pain syndrome of which only 18 had their diagnosis made by the treating physician.…”
Section: Discussionmentioning
confidence: 99%
“…Kumar et al. reported two cases of CRPS type I after open trauma hip surgery [ 6 ]. Commonalities with our case are gender (female), young age, and early start of symptoms after surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Commonalities with our case are gender (female), young age, and early start of symptoms after surgery. It was recommended to commence weight bearing at the earliest time possible [ 6 ]. Also, in our case, full weight bearing had a positive effect.…”
Section: Discussionmentioning
confidence: 99%